2019
DOI: 10.1029/2018jd029883
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Northern Stratosphere to the Madden‐Julian Oscillation During Boreal Winter

Abstract: In this study, the effects of the Madden‐Julian oscillation (MJO) on the northern stratosphere during boreal winter are investigated, especially in cases with the absence of a stratospheric sudden warming (SSW) event. During the wintertime, the polar cap temperature is expected to increase following MJO phase 2 (P2), P3, P4, and P7. However, the responses after P2 and P3 are much weaker if the dates from 50 days before to 50 days after the SSW central days are excluded from the composite. This result implies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
(77 reference statements)
2
13
0
Order By: Relevance
“…Significant warming also occurs after phases 4 and 5, which was not shown in G12. The results are similar to those of Yang et al (2019). The differences with the findings of G12 are probably due to the different choice of data sets, time period, and definitions of MJO events in this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Significant warming also occurs after phases 4 and 5, which was not shown in G12. The results are similar to those of Yang et al (2019). The differences with the findings of G12 are probably due to the different choice of data sets, time period, and definitions of MJO events in this study.…”
Section: Resultssupporting
confidence: 92%
“…(hereafter G12) found that midwinter SSW tends to follow certain MJO phases, which is due to the influence of the MJO on the North Pacific region that is strongly associated with tropospheric planetary waves. Previous studies both from reanalysis data and model simulations have confirmed a robust MJO-vortex connection and suggest an enhanced stratospheric heat flux related to the MJO (Garfinkel et al, 2014;Kang & Tziperman, 2017;Wang et al, 2018;Yang et al, 2019). Liu et al (2014) (hereafter L14) analyzed different MJO-SSW relationships for different types of SSW (i.e., vortex-displacement and vortex-split).…”
Section: Introductionmentioning
confidence: 99%
“…The MJO is the dominant mode of the tropospheric intraseasonal oscillation (ISO) (R. A. Madden & Julian, 1971, 1972b), and also has a considerable impact on tropospheric and middle atmospheric circulation and other dynamical processes. The tropical adiabatic heating induced by the MJO can enhance the quasi‐stationary wave activity in middle and high latitudes (Seo & Son, 2012; Yang et al., 2019). Therefore, major SSWs during Northern Hemisphere wintertime are also related to certain phases of the MJO (Garfinkel et al., 2014; Garfinkel, Feldstein, et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the MJO has a substantial impact on the extratropical circulation through the excitation of poleward propagating Rossby waves (e.g., Higgins & Mo, 1997; L'Heureux & Higgins, 2008; Lukens et al, 2017). Multiple studies have shown that MJO modulates the stratospheric polar vortex (Feng & Lin, 2019; Garfinkel et al, 2014; Garfinkel & Schwartz, 2017; Yang et al, 2019) and the occurrence frequency of sudden stratospheric warmings (SSWs) in the NH (Garfinkel et al, 2012; Liu et al, 2014; Wang et al, 2018). Garfinkel et al (2012) found that following MJO P3 (P7) a weakened (strengthened) polar vortex was found in the NH.…”
Section: Discussionmentioning
confidence: 99%